Euphrasia wettsteinii var. botniensium, comb. nov. (Orobanchaceae) - Piirainen, Mikko (Memoranda Societatis pro Fauna et Flora Fennica, 2020)
For updating the checklist of vascular plants of Finland, one new nomenclatural combination is proposed: Euphrasia wettsteinii G.L.Gusarova var. botniensium (Brenner) Piirainen.